2015
DOI: 10.3889/oamjms.2015.021
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum Cytokeratin-18 in Prediction of Hepatocellular Carcinoma in Chronic Hepatitis C Infected Egyptian Patients

Abstract: BACKGROUND:Hepatitis C virus is one of the most common etiologic agents of chronic liver diseases, including liver cirrhosis and hepatocellular carcinoma in which there is continuous inflammation and regeneration of hepatocytes. Cytokeratin-18 (CK18) has been suggested to play an important role in tumorigenesis of epithelial cancers.AIM:Estimation of CK18 serum levels in patients with chronic viral hepatitis C (CHCV) and hepatocellular carcinoma (HCC) and find the relationship between their levels, the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The current results indicated that there was nonsignificant change in numbers of WBCs among HCV, HCC, or control. This agrees with Aino et al (2014) and El-Zefzafy et al (2015) who reported that WBC count was not significantly changed in both HCC and HCV patients in comparison to the control individuals. The present results further indicated that the number of DCs generated from PBMCs of HCC patients was lower than that generated from control individuals or HCV patients.…”
Section: Discussionsupporting
confidence: 92%
“…The current results indicated that there was nonsignificant change in numbers of WBCs among HCV, HCC, or control. This agrees with Aino et al (2014) and El-Zefzafy et al (2015) who reported that WBC count was not significantly changed in both HCC and HCV patients in comparison to the control individuals. The present results further indicated that the number of DCs generated from PBMCs of HCC patients was lower than that generated from control individuals or HCV patients.…”
Section: Discussionsupporting
confidence: 92%
“…30 CK18 plays a key role in monitoring chronic viral hepatitis C, liver cirrhosis, and HCC. 31 The malignant transformation of cells can cause cells to secrete a large amount of HSP90α, which promotes the cell proliferation and metastatic potential. 32 TK1 is closely related to cell proliferation, and the up-regulation of TK1 is considered to be an early manifestation of cancer development.…”
Section: ■ Discussionmentioning
confidence: 99%
“…GP73 is highly expressed in HCC and promotes the tumor metastasis by inducing EMT in the hypoxic tumor microenvironment . CK18 plays a key role in monitoring chronic viral hepatitis C, liver cirrhosis, and HCC . The malignant transformation of cells can cause cells to secrete a large amount of HSP90α, which promotes the cell proliferation and metastatic potential .…”
Section: Discussionmentioning
confidence: 99%
“…El-Zefzafy et al showed CK-18 is a sensitive indicator of the severity of liver disease. Patients with CHC infection can be followed up by measuring serum levels of CK-18 which can predict the development of HCC (15).…”
Section: Discussionmentioning
confidence: 99%